A study on the independence of egocentric and allocentric neglect. (November 2017) - Turgut, Nergiz; Mödden, Claudia; Brumund, Tanja; Eling, Paul; Hildebrandt, Helmut
Abstract: Currently there seems to be consensus that visuospatial neglect may involve egocentric and allocentric symptoms. However, the relation between the two is still discussed and models have been proposed based on the high correlation between allocentric and egocentric neglect symptoms. To analyze the relation between these two kinds of symptoms we developed a new paradigm. In contrast to previous paradigms, we varied the extension of the search field and we added centered reference targets to evaluate egocentric effects independent from allocentric effects. Patients with exclusively left-sided neglect ( n = 15) and left-sided visual field deficit (VFD) ( n = 9) were included. Right brain damaged patients ( n = 15) and a healthy control ( n = 15) acted as control groups. The results revealed egocentric inattention in VFD patients. Neglect patients suffered from egocentric and allocentric neglect, but we found no interaction between both kinds of impairments in the sense of a monotonous additive or multiplicative increase going from right to left in terms of egocentric and allocentric coordinates. On the contrary, at the outmost left allocentric and egocentric positions, the number of omissions did not increase, unlike in outmost right and centered positions. In conclusion, our experiment shows that egocentric and allocentric neglect can be clearly dissociated in neglect patients and do not interact. Inclusion of neglect patients with a VFD may lead to an artificial interaction between egocentric and allocentric symptoms and this may explain the differences with results of previous studies.